Differences in Creative Thinking Ability of Vocational High School Students in Solving Contextual Mathematical Problems - Imaniar Resha Erfana; Hadi Kusmanto; Toheri (Ilmu Inovasi Nusantara, 2023)
In learning activities, various problems that are often encountered include students who still do not understand the material, or students abilities that are not yet clear, so that teachers find it difficult to apply appropriate learning. In this study, the aim was to obtain information about several aspects of students creative thinking skills in solving contextual mathematics problems for class XI SMK Islamic Center Cirebon. The population is 750 students, with a sample of 238 students. The type of research used in this research is quantitative, by analyzing the results in the form of numbers that are processed by statistical analysis. The findings of this study indicate that the students creative thinking ability shows that contextual mathematical problem solving is still in the very low category with an average value of 37,78. But in it there is an aspect of Elaboration with an average value of 61,13 which is in the medium category. Thus, in solving contextual mathematical problems, especially in Three Dimensional Geometry, the ability to think in detail is sufficient when making image objects that are easier to understand from the illustrations provided. Therefore, the ability to think in the Elaboration aspect must be maintained and the Fluency, Flexibility, and Originality aspects must be further improved. The results showed that there were significant differences between the ability to think creatively with each major, including the best major is Accounting and Financial Institutions (AKL). Teachers can maintain relationships with fellow teachers and establish better communication so that mathematics learning is achieved even though students come from different majors